War girls : the First Aid Nursing Yeomanry in the First World War (MANCHESTER UNIV Press, 2017)
War Girls reveals the fascinating story of the British women who volunteered for service in the First Aid Nursing Yeomanry during the Great. Examining their experiences on the Western Front with the Belgian, British and French Armies, this book shows how the FANY worked as nurses and ambulance driver-mechanics, inspiring stories of female heroism and solidarity. The FANY created skilled gendered performances against the cultural myths of the time, and in concert with their emerging legend. Coming from privileged backgrounds, they drew upon and subverted traditional arrangements, crafting new an.